Analisis Sistem Spasial Keraton Ismahayana Landak dengan Pendekatan Space Syntax - Fitri Prawitasari; Heri Pramono; Ya’ Mohamad Syarif (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Ismahayana Palace is one of the archaeological evidences of traditional houses from the Landak Kingdom era found in Raja Village, Ngabang to this day. The existence of the Ismahayana Palace as a characteristic traditional house is a cultural manifestation that reflects the richness of an ethnic group and local wisdom that needs to be preserved. The spatial system is one way to identify characteristics related to spatial arrangement, spatial structure, spatial direction, and spatial interrelationships. This study uses a quantitative method with a space syntax approach supported by descriptive analysis and simulation using UCL DepthmapX-0.8 software to reveal the connection, integration, and accessibility between spaces. The results of the Axial Line analysis show a highly structured circulation pattern, with the hallway as a global integration path (RN: 0.92) and the highest connectivity point (connectivity: 7). The Balairung (RN: 0.75) functions as a semi-public space, while the heirloom room (RN: 0.30) and kitchen (RN: 0.25) show high spatial segregation. Visibility Graph Analysis (VGA) analysis supports these results, with the highest visibility in the hallway (isovist: 210 m², connectivity: 45), and low visibility (<60 m²) in private spaces. The findings indicate that the palace's spatial design is not only functional but also shapes and reinforces social structures and interaction patterns. The space syntax approach has proven effective in revealing the relationship between accessibility, visibility, and spatial function in the context of traditional architecture.